Zakat Management At The National Zakat Agency Of Tegal District - Nurul Fitri Habibah (Journal Arbitrase : Economy, Management and Accounting, 2023)
This study aims to determine the management of zakat management at the national amil zakat agency of tegal regency. The method used in this research is descriptive qualitative and the data collection technique is done by field research (field), which is done by digging up data sourced from the location or research field, in this study sourced from BAZNAS tegal district. The results obtained in this study are the increase in the amount of zakat funds collected by the Zakat Collection Unit as an implementation of performance optimization carried out by BAZNAS Tegal Regency. In 2022 the Zakat fund reached the amount of Rp. 4,126,034,293, the majority of the funds were collected from ASN employees. The awareness of people in paying zakat still assumes that people can pay zakat themselves, even though the more zakat collection to the organization the greater the distribution, the greater the distribution the more people benefit, the more people benefit the smaller the unemployment and poverty rates by involving management functions in it.